The systemic risk buffer for UK banks: a response to the Bank of England's consultation paper - Vickers, J (Oxford University Press, 2016)
The article responds to the Bank of England’s (BoE) consultation paper of January 2016 on the systemic risk buffer for UK ring-fenced banks. It argues that, contrary to its proposed policy, the BoE should apply the highest permitted buffer rate—3 per cent of risk-weighted assets of common equity—to all large ring-fenced banks. The BoE’s reasons for lowering its estimate of optimal equity capital requirements are assessed critically.